PERAN MAJELIS KEHORMATAN DISIPLIN KEDOKTERAN INDONESIA (MKDKI) TERHADAP DUGAAN KELALAIAN MEDIS DOKTER - Sapta Aprilianto (Universitas Airlangga, 2015)
Governments in Indonesia have sought a protection under the law to create a harmony of doctor-patient relationships. The establishment and the realization of special assemblies in the medical field in Indonesia such as KKI, MKDKI and MKEK is proof that the government is serious about the existing problems. In accordance with a headline about the existence of MKDKI Against Medical Error Doctor, then target the results of this paper to be used as guidance for the people and anyone who is legal interests harmed by the actions of medical mal doctor. Medical Practice Act governing the duties and authority MKDKI, but menaknisme complaints should be clarified through this tuisan following characteristics rather than the actions of doctors assessment of medical errors. According to the Act the medical field in Indonesia do not use the term negligence when using a term that includes the Medical Disciplinary Violations violation of professional standards, violations of operational procedures and violation of service standards. On the other hand the results of this paper can be a reference for the development of health law, especially with regard to the mechanism of settlement of the criminal case of medical error doctor.